Does Size Still Matter? Change in Continuous Relation Between Audit Firm Size and Audit Quality in China Post IFRS Convergence - Tairan Huang; Ge Zhang (Australasian Accounting Business and Finance Journal, 2024)
Our study replicates Li (2008) in a new context. According to the Deep Pocket Theory (DPT), smaller or less financially robust audit firms may face challenges in competing with larger, deep-pocketed firms in terms of audit quality (DeAngelo, 1981; Dye, 1993). Accordingly, we empirically re-examine the relationship between audit firms and audit quality in the context of China's developing audit market, between 2017-2019. Following Li (2008), we build a regression model with modified opinion as the dependent variable. Specifically, we use three different measures, including assets, sales, and revenues, to quantify audit firm size, while taking steps to address potential confounders and endogeneity. The sample we used has characteristics that match the original literature. Our results suggest that the Chinese audit market has changed dramatically and that the previously observed positive association between audit firm size and audit quality, as reported by Li (2008), no longer retains statistical significance in the contemporary Chinese audit environment. Our result remains robust even when private and foreign joint venture audit firms are excluded, highlighting the importance of revisiting related topics. Our contribution is to provide new empirical insights into the complex relationship between audit firm size and audit quality in the unique context of China's evolving audit market. Furthermore, it discusses the implication of the reported non-significant results and justifies the replication.
Keywords: Audit Quality; Audit Firm Size; Deep Pocket Theory; Replication